Ensuring Success for Grieving Nursing Students through Mentorship and Community - Morgan Yordy; Stephanie Wood; Chih-Hsuan Wang (The Ohio State University Libraries, 2024)
Background: Approximately 22-30% of undergraduate college students have experienced the loss of a loved one within the last year, and almost 50% within the last two years. A College of Nursing located in the Southeastern United States saw an increase in students experiencing an immediate family member loss. The demanding curricula and clinical experiences encountered by these students further heighten grief symptoms and social isolation. Aim: This study aimed to develop a tailored program to provide resources and a support system to nursing students who have experienced loss and grief. Methods: This study employed a quasi-experimental design with two data collection points. Relationships, self-esteem, purpose, and optimism relating to grief symptoms were assessed pre-and-post program using the Flourishing Scale. Due to the limited sample size, the Mann-Whitney U nonparametric test was used to assess differences in Flourishing scores. Results: The results indicated no significant differences between the pre-and-post Flourishing Scale scores. However, participant feedback towards the support group was positive. Conclusion: Grief groups tailored to nursing students provide an important community of support that maintains positive student health and well-being.